Arabic Language Learning Based on Local Wisdom within the Framework of Global Citizenship Education - Arif Widodo (Jurnal Inovasi Pembelajaran dan Pendidikan, 2025)
Arabic language learning in pesantren (Islamic boarding schools) generally focuses on understanding linguistic structures and analyzing traditional religious texts, while the integration of relevant values and global issues remains minimal. This research aims to conceptually explore the possibility of incorporating the local wisdom of pesantren into Arabic language teaching as a means to strengthen Global Citizenship Education. The research method employed is a literature study, examining international journal articles, research books, reports from international agencies, and studies related to pesantren education and language pedagogy. The findings indicate that the values of pesantren local wisdom such as tawassuth (moderation), tasamuh (tolerance), musyawarah (deliberation), and tata krama (etiquette) possess strong relevance to the cognitive, socio-emotional, and behavioral dimensions of GCE. The novelty of this research resides in the integrative synthesis of Arabic language learning, pesantren local wisdom, and Global Citizenship Education, while its originality is reflected in positioning the pesantren as an alternative locus for global education that remains under-explored in international discourse.